Pencegahan Penyebaran Corona Virus: Sosialisasi GERMAS Di Desa Perdamean, Tapanuli Tengah - Paskalina Sinulingga; Pristi Suhendro Lukiyoto; Prihatin Ningsih Sagala (Program Studi Pengembangan Masyarakat Islam, 2020)
One of the Tridarma of Higher Education is community service which is usually outlined in the Real Work Lecture program every year. In 2020 the focus of KKN activities is on preventing the spread of Coronavirus which causes respiratory tract infections in humans. The spread of the virus is getting faster in Indonesia, but there is still a lack of understanding and awareness from the community in Pardamean Village, Sorkam District, Central Tapanuli Regency. Therefore there is a need to increase understanding of the Coronavirus and preventive measures, one of the steps to prevent it is to carry out the Healthy Living Community Movement (Germas). Based on this, a socialization on Coronavirus and Germas was held as a small step to prevent Coronavirus to the people of Pardamean Village. In addition to the socialization, there was also a ban on and spraying of disinfectants in the village environment and conducting exercise activities in the morning. This activity was successfully carried out by seeing the enthusiasm of the community in participating in the Germas socialization and applying it in their daily lives